Catalyzed silanization by supporting ceria on silica towards rubber composites with improved mechanical properties. (June 2022) - Zhang, Chengfeng; Yu, Shuangjian; Tang, Zhenghai; Guo, Baochun
Abstract: The silane modification in silica-filled rubber composites is essential to fulfil the potentials of silica. However, the silanization efficiency of silica generally remains unsatisfactory. Promoting silica silanization contributes to not only the improvements on composite properties, but also the reduction in volatile organic compound emissions during processing. In this work, we present a novel way to promote silica silanization in rubber composites by supporting ceria nanocrystals on silica surface. Specifically, silica supported with varied ceria nanocrystal loading is synthesized and used as a novel reinforcement for styrene-butadiene rubber. Model compound experiments demonstrate that the ceria on silica surface can effectively promote the silanization reaction based on its unique acid-base property. Due to the promoted silica silanization, silica dispersion is greatly improved and interfacial interaction is remarkably enhanced in the composites. Accordingly, the resulting composites filled with ceria-anchored silica exhibit desirable improvements on the tensile modulus and dynamic mechanical properties, which is conductive to tire application. Graphical abstract: Image 1 Highlights: Silica supported with ceria (Ce–SiO2 ) shows catalytic reactivity for silanization. Silica dispersion and interfacial adhesion in composites are improved due to the promoted silanization. Mechanical properties of rubber composites filled with Ce–SiO2 are improved.